Pelatantheria woonchengii, a new addition for the Orchid Flora of Vietnam - Truong, Vuong Ba (2018)
Pelatantheria woonchengii is a new record for the orchid flora of Vietnam. This species was previously misidentified as Pelatantheria ctenoglossum Ridl., as both species are present in Vietnam. The illustration, description, distribution and comparison with the closest species in Vietnam are included An updated identification key for all Vietnamese members of the genus Pelatantheria is presented.